Developing and Utilizing a Next-Generation Humanized Mouse Model for Investigating HIV and Tuberculosis - Lepard, Madeleine (My University, 2022)
Currently, there are 38 million people living with human immunodeficiency virus (HIV-1) worldwide and there were 680,000 HIV-related deaths in 2020 alone. The greatest cause of mortality in people living with HIV (PLHIV) is infection with opportunistic pathogens such as tuberculosis (TB), which accounts for one third of HIV-related deaths. PLHIV are 20 times more susceptible to TB and co-infection leads to significantly worsened outcomes in terms of both diseases. Humanized mouse (hu-mouse) models, which possess human immune cells for HIV to infect, have been useful for HIV research. Our aim is to create hu- mouse models of HIV, TB and co-infection to investigate disease progression, immune responses, therapeutics, prevention and vaccination. NOD-Rag1null-IL2rgnull (NRG) mice are highly immunocompromised mice that are traditionally used to generate hu-mouse models. We are also developing NRG mice that are transgenic for human HLA-DR4 and HLA-A2 (DRAG-A2) and similar mice have been reported to have improved immune responses. NRG and DRAG-A2 mice were humanized with hematopoietic stem cells obtained from human umbilical cord blood. DRAG-A2 mice had significantly higher engraftment success rates (defined as the percentage of mice with >10% hCD45+) as well as higher overall CD45+ leukocyte, CD4+ T cell, CD19+ B cell and CD14+ monocyte reconstitution in the blood compared to huNRGs. huNRG mice were permissive to infection with JR-CSF or NL4.3-Bal-Env HIV-1 intravaginally or systemically. huDRAG-A2 mice were also infected intravaginally with NL4.3-Bal-Env HIV-1. huDRAG-A2 mice, but not huNRGs, produced HIV-specific IgG, indicating improved immune responses. huNRG mice were infected intranasally with mCherry-Erdman, YFP-H37Rv or H37Rv Mtb. huDRAG-A2 mice were also infected with H37Rv. Human immune cell involvement and human-like granuloma formation was observed using flow cytometry and immunohistopathology. These findings show that the DRAG-A2 model may be optimal for investigating HIV, TB and co-infection, which continue to be serious global health concerns.
Infection & Immunity
Keywords: HIV; TB; Humanized mice; Co-infection